MARRIAGE AGREEMENT FOR THE JOINT ASSETS IN MIXED COUPLE MARRIAGE ACCORDING IN INDONESIA BOOK OF CIVIL LAW NUMBER 1 OF 1974 POST DECISION OF THE COURT OF CONSTITUTION NUMBER 69/PUU-XIII/2015 - Tutik, Titik Triwulan (International Journal of Research -GRANTHAALAYAH, 2021)
This study aims to analyze the position of the Marriage Agreement for Joint Treasures in Mixed Marriage from three sides of the law, namely Civil Law, Law Number 1 of 1974, and Constitutional Court Decree Number 69/PUU-XIII/2015. Hypothesis: Decision of the Constitutional Court Number 69/PUU-XIII/2015 in line with Islamic law that prioritizes equal rights and obligations between husband and wife in terms of ownership of assets in marriage. The method: used is normative (dogmatic) legal research, which is intended to find and formulate legal arguments, through analysis of the subject matter. While the approach used in this study there are 4 (four) types, namely: the statutory approach, comparative approach, conceptual approach, and case approach. The results: of the study show that the Constitutional Court Decision Number 69/PUU-XIII/2015 has provided a practical solution in overcoming the problems of a Marriage Agreement on Joint Assets: First, a marriage agreement can be made before, during and after the marriage is implemented. Second, ratification of a marriage agreement may be by a notary public, and effective from the date of the marriage agreement, and may be revoked. Third, marriage agreements are binding on third parties, especially related to the position of joint property in the marriage. This means that, Indonesian citizens have the right to joint property in a mixed marriage as long as the marriage agreement states that. The ruling is in line with Islamic law that prioritizes equal rights and obligations between husband and wife in terms of ownership of assets in a marriage. Conclusion: The legal consequences of the Constitutional Court Decision Number 69/PUU-XIII/2015 on the status of joint property made a marriage agreement after marriage which began since the marriage took place followed by the status of shared property becomes separate if both parties wish in the agreement, as well as assets to be obtained in the future remain the property of each party, without having to obtain a court decision regarding the separation of assets. This ruling is in accordance with Islamic law which prioritizes equal rights and obligations between husband and wife in terms of ownership of assets in marriage.